PENINGKATAN MUTU PEMBELAJARAN PPKn DALAM PEMBENTUKAN KARAKTER SISWA DI MAN 1 MODEL KOTA BENGKULU - Minarni Minarni (Universitas Islam Negeri Fatmawati Sukarno, 2018)
Teacher Learning Quality Improvement of PPKn in forming Student Character in Bengkulu City 1 Model. The results of this study indicate that Teacher PPKn’s Learning Quality Improvement in forming Student Character in Bengkulu City Model 1 is done by giving more attention when there is free time and maximizing that time so that the meeting becomes quality for students. , rational, emotional and supporting factors are the existence of motivation and good cooperation between the school and parents, joint commitment, availability of facilities to support the learning process better. The inhibiting factor is the background of different students, lack of awareness of students, innate or hu- man nature, environment in association